Creation of a Custom 3D Algorithm for Proper Alignment of Straight Nails in Tibiotalocalcaneal Arthrodesis - Omer Subasi PhD; Wei Shao Tung BS; Julian Hollander Bsc; Samir Ghandour MD; Atta Taseh MD; Nour Nassour MD; Adarsh Aratikatla; Alireza Ebrahimi MD; Bernard Burgesson MD; Soheil Ashkani-Esfahani MD; John Y. Kwon MD (Foot & Ankle Orthopaedics)
Category: Hindfoot; Ankle Introduction/Purpose: Tibiotalocalcaneal (TTC) arthrodesis is a complex procedure for severe ankle and hindfoot pathologies like end-stage osteoarthritis or avascular necrosis of the talus. Proper calcaneal fixation with the talus and tibia is crucial for postoperative stability and neurovascular protection in intramedullary nailing. A cadaveric study by Hyer et al. showed that a wire placed anterograde through the tibial shaft may miss the calcaneus medially. Methodologic limitations included a limited number of cadavers, non-loaded specimens, and a lack of critical examination of hindfoot alignment. This study aims to determine the feasibility of using weightbearing computed tomography (WBCT) and 3D segmentation software to ascertain an optimal entry point for a straight intramedullary nail in TTC arthrodesis in weightbearing patients. Methods: A total of 100 normal ankles (48 left, 52 right) from 52 patients (Age: 39.9 ± 16.7 years; Gender: 68% F; BMI: 28.1 ± 5.8 kg/m^2) with WBCT scans were obtained and subsequently segmented for inclusion in the study. A novel mathematical algorithm was developed to determine the 3D intersection of the distal tibial central axis extension at the inferior calcaneus. The algorithm approximates the central axis by mapping the center point of the tibial medulla at each CT slice, from the shaft to the tibiotalar joint using 3D surface contours in the axial plane. Then, the central axis is extended through the talus and calcaneus to approximate its exit point on the inferior surface of the calcaneus for each individual ankle (Figure 1a). A 2D linear transformation (affine transformation) was applied to obtain a heat map of all intersection points on the inferior surface of the calcaneus. Results: The mean (SD) polar angle of the central axis with respect to the ground was 84.9 ± 2.3 degrees. The root mean (SD) square error of the affine transformation was 1.62 ± 1.02 mm, demonstrating the validity of mapping. The exit points of the central axis across all patients fall predominantly along the sustentaculum tali (Figure 1b). Conclusion: A straight nail passing through the sustentaculum tali places surrounding neurovascular structures at risk and can also compromise the biomechanical stability of the implant. Our novel 3D algorithm shows that intraoperative adjustment of the starting point lateral to the central tibial axis is required to obtain optimal alignment of the hindfoot nail. Additionally, the novel algorithm can also be used preoperatively to estimate the required calcaneal medialization and ensure precise implant positioning. Proper nail alignment may potentially improve the success of TTC arthrodesis and decrease the risk of postoperative complications, including implant failure.